FEATURES A LIVING MANAGEMENT IN A GLOBALIZING WORLD - V. Ukolov; V. Kostryukov (Вестник университета)
The necessity to change the current management concepts in a globalizing world. The necessity of the use of live control to save humanity and give it adequate development momentum. It proved the feasibility of the return of people to preserve the cultural and spiritual roots of the multinational people of the world. We give particular live control, which can be used in the process of adoption of global administrative decisions.